2019
DOI: 10.1029/2018ja026225
|View full text |Cite
|
Sign up to set email alerts
|

SuperDARN Evidence for Convection‐Driven Lagrangian Coherent Structures in the Polar Ionosphere

Abstract: Polar cap patches are large sporadic enhancements of plasma density on the scale of hundreds of kilometers, which can impact the performance of Global Navigation Satellite Systems. Lagrangian Coherent Structures (LCSs) are ridges that show areas of maximal separation in a time‐evolving flow. Previous work based on modeled ionospheric flow showed that LCSs exist in the ionosphere and are barriers governing patch formation. In this work, we identify the first data‐driven LCSs in the high‐latitude ionosphere usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…(2017) found that a lower thermospheric LCS may have acted as the poleward barrier of space shuttle water vapor plume transport. The LCSs in modeled plasma drifts were found to be a necessary condition for the formation of the polar cap patch (Wang et al., 2018), then further supported by data‐assimilated ionospheric convection (Ramirez et al., 2019). Both T‐LCSs and I‐LCSs appear at middle‐to‐high latitudes and respond to geomagnetic disturbances by shifting equatorward and growing more complex.…”
Section: Introductionmentioning
confidence: 81%
“…(2017) found that a lower thermospheric LCS may have acted as the poleward barrier of space shuttle water vapor plume transport. The LCSs in modeled plasma drifts were found to be a necessary condition for the formation of the polar cap patch (Wang et al., 2018), then further supported by data‐assimilated ionospheric convection (Ramirez et al., 2019). Both T‐LCSs and I‐LCSs appear at middle‐to‐high latitudes and respond to geomagnetic disturbances by shifting equatorward and growing more complex.…”
Section: Introductionmentioning
confidence: 81%
“…Interested readers may refer to Figure 1 of Ramirez et al. (2019) for an illustration of the terms in Equation 2. For a fluid element at x0, the amount of stretching it undergoes can be measured by the FTLE, the largest singular value of boldJ: σ(J)=1false|τfalse|log(λmax(JTboldJ)) …”
Section: Introductionmentioning
confidence: 99%
“…Interested readers may refer to Figure 1 of Ramirez et al (2019) for an illustration of the terms in Equation 2. For a fluid element at 0…”
mentioning
confidence: 99%
“…To validate convection maps, some authors have used ionospheric F-region electron density structures as a tracer of the ExB drift. Wang et al (2018) and Ramirez et al (2019) have used the observed motion of high-latitude electron density structures to assess the accuracy of Weimer's (2005) empirical model and Ruohoniemi and Baker's (1998) SuperDARN-driven high-latitude potentials. For this investigation, we will use in situ plasma drifts and GPS-derived total electron content (TEC) data to test the validity of high-latitude potential solutions.…”
mentioning
confidence: 99%